2020
DOI: 10.1111/jen.12742
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota ofSpodoptera frugiperda(J.E. Smith) larvae as revealed by metatranscriptomic analysis

Abstract: The invasive fall armyworm, Spodoptera frugiperda (J.E. Smith; Lepidoptera: Noctuidae), is considered one of the most harmful pests in corn, rice and cotton crops and has developed resistance to the most widespread methods used to control it, chemical insecticides and transgenic crops based on Bt toxins. On the other hand, gut microbiota plays an important role in the insect's fitness, and metatranscriptomic analyses of the insect host are an invaluable tool for identifying new pest control targets. Notwithsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 81 publications
4
35
0
Order By: Relevance
“…This finding corroborates the recent report by Rozadilla et al (2020) who also detected the presence of archaea in the gut of S. frugiperda larvae using high-throughput pyrosequencing of 16S rDNA, and it represented a high proportion of the metabolically active gut microbiota in S. frugiperda. Archaea have been revealed through metagenomic studies to be very diverse and prolific, and they play vital roles in nitrogen cycling in soils (Bates et al, 2011;Edwards et al, 2015;Siles, Öhlinger, Cajthaml, Kistler, & Margesin, 2018;Secil, Sevim, Demirbag, & Demir, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This finding corroborates the recent report by Rozadilla et al (2020) who also detected the presence of archaea in the gut of S. frugiperda larvae using high-throughput pyrosequencing of 16S rDNA, and it represented a high proportion of the metabolically active gut microbiota in S. frugiperda. Archaea have been revealed through metagenomic studies to be very diverse and prolific, and they play vital roles in nitrogen cycling in soils (Bates et al, 2011;Edwards et al, 2015;Siles, Öhlinger, Cajthaml, Kistler, & Margesin, 2018;Secil, Sevim, Demirbag, & Demir, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, a study in Kenya using NGS reported 19 major bacteria genera in the gut of S. frugiperda (Gichuhi et al, 2020). The fifth report on S. frugiperda Argentina using high-throughput pyrosequencing of 16S rDNA reported 10 major bacteria genera with other non-bacterial group (Rozadilla et al (2020). In the present study, 20 major bacterial genera were documented.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations